Biomarker and Companion Diagnostics—A Review of Medicinal Products Approved by the European Medicines Agency - Orellana García, Laura Patricia; Ehmann, Falk; Hines, Philip A.; Ritzhaupt, Armin; Brand, Angela (Frontiers in Medicine, 2021)
Background: An increasing number of medicines authorised in Europe recommend or require biomarker-based patient selection. For some of these the use of a companion diagnostic (CDx), a subset of in vitro diagnostics (IVDs), to identify patient populations eligible for a specific medicinal product may be required. The information and recommendations of use of a medicinal product for which a CDx is required is particularly important to healthcare professionals for correct patient identification. Methods: We reviewed the existing information in SmPCs and European Public Assessment Reports (EPARs) of EU medicinal products approved via the centralised procedure at EMA where reference was made to biomarker testing, including by CDx, for patient selection. Results: The results show that varying levels of detail are provided for the biomarker and the diagnostic test, including variability in where the information was presented. The overall results demonstrate transparent but sometimes heterogeneous reporting of CDx in the SmPC and EPAR. Conclusions: With the introduction of the new Regulation (EU) 2017/746 on in vitro diagnostic medical devices, medicines regulatory authorities' will be required to be consulted during the review of CDx conformity assessment and so, there is opportunity for more consistent and transparent information on CDx to be provided in the SmPC and EPAR.